A systematic study of cross-border M&As: uncovering how Chinese MNEs gain benefits - Zhao, Haoyu (2025)
Although Cross-border M&As (CBMAs) are a popular strategy, only a minority of firms have achieved significant success. In response to this issue, this thesis explores the influence factors on Chinese multinational enterprises' (MNEs) CBMAs premiums and post-CBMAs performance, aiming to identify the contingent factors that enable Chinese MNEs to enhance their global competitiveness.